Faktor-Faktor yang Memengaruhi Pemilihan Pinjaman dengan Sistem Rente di Desa Studi Kasus : Desa Panulisan Timur Kecamatan Dayeuhulur Kabupaten Cilacap (Periode Tahun 2013-2014) - Prawito Hudoro; Muhammad Findi A; Salahuddin El Ayyubi (AL-MUZARA'AH, 2014)
Rente loan system is a loan scheme that is based on interest. This loan system is widely used by the Micro and Small Medium Enterprises (SME) notably in particular rural communities. The purpose of this study is to analyze the development process and system received rents in the Panulisan Timur District of Dayeuhluhur Regency of Cilacap, and analyze the factors that affect the selection of loan seeking system. The method used in this study is a qualitative method with a case study approach. The data used is primary data obtained through observation and interviews to the villagers of the Panulisan Timur District of Dayeuhluhur Regency of Cilacap uses rente system. The study was conducted during the period December 2013 to April 2014. Number of key informants in this study were 5 people and the number of respondents 30 people. The results showed that the loan scheme growing rents in the Panulisan Timur District of Dayeuhluhur Regency of Cilacap consists of the active and passive processes. The existence of internal factors such as the need for cash is urgent and external factors in the form of an easy loan terms, the availability of funds every day, disbursement fast and easy access makes the transaction rents to survive and be accepted by society.